Caste and Gender in Relation to Health Inequality: A Village Study from Kerala. (February 2017) - Scaria, Suma
This article is based on a micro-level village study in Kerala, the southernmost Indian state with its long-standing impressive basic indicators in health, economic growth and social development. Using the theoretical perspective of 'cultural inflation of morbidity' for a hypothesis of continuing inequities in health outcomes, it examines how far such impressive basic indicators have actually translated into equity in health outcomes, defined in terms of incidence of morbidity and morbidity pattern. Confirming the hypothesis, the findings discuss to what extent both caste and gender, separately and together, may be continuing today to mediate health outcomes in a changing socio-economic environment.